The use of neuroimaging in dementia by Irish general practitioners. (August 2016) - Ciblis, A.; Butler, M.-L.; Bokde, A.; Mullins, P.; McNulty, J.
Abstract Background More than 48, 000 people in Ireland are living with dementia, and the number is likely to rise to 130, 000 by 2041. Dementia frequently remains undiagnosed, depriving many of early interventions and the opportunity to plan for the future. Neuroimaging is helpful in the diagnosis of dementia, yet it is often insufficiently utilised. General practitioners (GPs) often decide which patients should be referred on for specialist assessment and as such play a crucial role in dementia diagnosis. Aims To establish the accessibility of neuroimaging in dementia by GPs, current referral patterns, confidence in referral and opinions on radiology reports. Methods The research design was a postal survey among GPs in single and group practices in urban, rural and semi-rural areas in the east and southeast of Ireland. GPs were identified from the Irish Medical Directory and posted individual anonymous questionnaires. Results A third of participants reported that they had no direct access to neuroimaging. Access differed between public and private patients. GPs primarily referred to computed tomography and magnetic resonance imaging, but only 14.6 % based these referrals on published guidelines. A total of 47.8 % of participants were not very confident in their ability to choose the most appropriate modality. Conclusion Access to neuroimaging investigations for suspected cases of dementia varies between locations and public and private systems. To improve diagnostic rates and ensure appropriate utilisation of imaging resources, GPs require access to clinical and referral guidelines to ensure appropriate use of neuroimaging and the best possible patient outcomes.